2000
DOI: 10.1091/mbc.11.12.4117
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Cyclin/cdk Phosphorylation Sites in HsCdc6 Disrupts a Late Step in Initiation of DNA Replication in Human Cells

Abstract: Cyclin-dependent kinases (Cdk) are essential for promoting the initiation of DNA replication, presumably by phosphorylating key regulatory proteins that are involved in triggering the G1/S transition. Human Cdc6 (HsCdc6), a protein required for initiation of DNA replication, is phosphorylated by Cdk in vitro and in vivo. Here we report that HsCdc6 with mutations at potential Cdk phosphorylation sites was poorly phosphorylated in vitro by Cdk, but retained all other biochemical activities of the wild-type prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 54 publications
1
29
2
1
Order By: Relevance
“…Human Cdc6 contains three consensus cdk phosphorylation sites within an amino terminal domain, and several studies have demonstrated that phosphorylation of Cdc6, most likely by cyclin A͞Cdk2, leads to its export from the nucleus to the cytoplasm, presumably to prevent reinitiation of replication in G 2 (19)(20)(21). In addition, Herbig et al (39) and Jiang et al (21) also have suggested that phosphorylation of Cdc6 may play a positive role in Cdc6 function because overproduction or microinjection of a mutationally altered Cdc6 that cannot be phosphorylated by cdks blocked DNA replication. In contrast, Petersen et al (20) and Pelizon et al (19) performed similar experiments but observed no consequences of the lack of Cdc6 phosphorylation other than a failure to relocalize Cdc6 during S phase.…”
Section: Prereplication Complex Formation Occurs In the Absence Of Cdkmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Cdc6 contains three consensus cdk phosphorylation sites within an amino terminal domain, and several studies have demonstrated that phosphorylation of Cdc6, most likely by cyclin A͞Cdk2, leads to its export from the nucleus to the cytoplasm, presumably to prevent reinitiation of replication in G 2 (19)(20)(21). In addition, Herbig et al (39) and Jiang et al (21) also have suggested that phosphorylation of Cdc6 may play a positive role in Cdc6 function because overproduction or microinjection of a mutationally altered Cdc6 that cannot be phosphorylated by cdks blocked DNA replication. In contrast, Petersen et al (20) and Pelizon et al (19) performed similar experiments but observed no consequences of the lack of Cdc6 phosphorylation other than a failure to relocalize Cdc6 during S phase.…”
Section: Prereplication Complex Formation Occurs In the Absence Of Cdkmentioning
confidence: 99%
“…We also provide evidence that phosphorylation of Cdc6 is not required for Mcm chromatin loading. Previous studies have offered conflicting data on this point with some investigators reporting no consequences (19,20) whereas others report a dominant interfering effect and suggest that phosphorylation of Cdc6 is required for origin firing (21,39). Possible explanations for the discrepancies between these studies include differences in the form of Cdc6 that is overproduced, particularly when it is expressed as a fusion protein, or the extent to which Cdc6 is overexpressed.…”
Section: Mammalian Cdc6 Induces MCM Chromatin Associationmentioning
confidence: 99%
“…It is well established that the stability of Cdc6 protein is regulated by phosphorylation at 3 canonical CDK sites within its N-terminal domain, 8,9 which depends on acetylation by the acetyltransferase GCN5 at specific residues nearby. 10 In quiescent mammalian cells the anaphase promoting complex (APC) E3 ubiquitin ligase provides for constant proteasomal degradation of Cdc6.…”
Section: Introductionmentioning
confidence: 99%
“…In middle to late G 1 and at the G 1 /S transition, S-phase cyclins (cyclin E and cyclin A) and cdk2 are expressed (21,22) and initiate DNA replication by phosphorylating CDC6, which causes it to dissociate from Pre-RC (23). Release of CDC6 from chromatin and its translocation to the cytoplasm triggers initiation of DNA replication (24). Another role of CDC6 in S. cerevisiae is to function as an inhibitor of the G 2 /M phase until the S phase is complete (25).…”
mentioning
confidence: 99%